Outcome of two cohorts with nephroblastoma treated with consecutive International Society of Paediatric Oncology protocols in a South African paediatric oncology unit - Reddy, Kershinee (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPhil)--Stellenbosch University, 2022.